Translation Procedures in Subtitles of Back To The Outback Movie - Ni Luh Arintya Sumertiasih; I Nyoman Aryawibawa; I Gusti Agung Istri Aryani (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This research aims to analyze the translation procedures applied in the English-Indonesian subtitles of the animated film Back to the Outback, with a particular focus on how these procedures contribute to conveying meaning appropriately across languages and cultures. Using a descriptive qualitative approach, the study examines utterances and sentences from both the English and Indonesian subtitle versions, which were sourced from the Subscene platform, a site where users collaboratively translate films into various languages. Data collection involved watching the film while observing the subtitles in both languages, followed by identifying and categorizing the translation procedures based on Peter Newmark’s theoretical framework. The findings reveal that the subtitles employ ten out of Newmark's nineteen translation procedures: couplet, modulation, paraphrase, reduction, literal translation, cultural equivalent, transfer, functional equivalent, naturalization, and transposition (shift). These procedures reflect the translator’s efforts to retain meaning, tone, and cultural nuance, making the film accessible and relatable to Indonesian audiences. Furthermore, the study concludes that the target audience of Back to the Outback includes viewers of all age groups, supported by the universal and comprehensible nature of the subtitle translation.